Shape Shifting Masculinities: Accounts of maleness in Indian man-to-animal transformation horror films - Dhusiya, Mithuraaj (Acta Orientalia Vilnensia, 2011)
University of Delhi Unlike the werewolf myth, on which there is a significant corpus of takes in Hollywood cinema, Indian horror films abound in snake-, tiger- and gorillatransformations. Most of these shape-shifting monsters represent aberrant subjectivities that set in motion a cycle of destruction and redemption within these narratives. This article will explore how the male body in Indian horror films acts as a site of different bodily discourses that permits a reading of socio-cultural crises within the societal framework. Although there are almost a dozen Indian horror films to date that deal with such shape-shifting monsters, this article will limit itself to studying one Hindi film Jaani Dushman (1979, dir. Raj Kumar Kohli) and one Telugu film Punnami Naagu (1980, dir. A. Rajasekhar). The following core questions will be explored: do these narratives challenge the constructions of hegemonic masculinity? What departures from normative masculinity, if such a thing exists at all, take place? How do these narratives use horror codes and conventions to map the emergence of different types of masculinities? How can these bodily discourses be correlated with various contemporary socio-political issues of India?